Managing Social Media and Consumerism The Grapevine Effect in Competitive Markets - Rajagopal. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Categorically reviews the theories of communication, best practices in social media and previous research, and analyzes the corporate involvement towards strategic and tactical stewardship in serving customer-centric business requirements.